2006
DOI: 10.1080/09537100500460234
|View full text |Cite
|
Sign up to set email alerts
|

Expression of functional recombinant mosquito salivary apyrase: A potential therapeutic platelet aggregation inhibitor

Abstract: Excessive platelet activation and accumulation can lead to vessel occlusion and thus present major therapeutic challenges in cardiovascular medicine. Apyrase, an ecto-enzyme with ADPase and ATPase activities, rapidly metabolizes ADP and ATP released from platelets and endothelial cells, thereby reducing platelet activation and recruitment. In the present study, we expressed a 68-kDa recombinant mosquito (Aedes aegypti) salivary apyrase using a baculovirus/insect cell expression system and purified it to homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 38 publications
1
46
0
1
Order By: Relevance
“…Apyrase is an ectoenzyme that rapidly metabolizes ADP and adenosine triphosphate (ATP) released from activated platelets and endothelial cells, thereby minimizing ADP-dependent platelet activation and recruitment. 38 Apyrase treatment had no effect on platelet accumulation in anti-GBM antibody-treated mice ( Figure 9A). In contrast, apyrase treatment significantly decreased the number of adherent leukocytes in response to anti-GBM antibody ( Figure 9B).…”
Section: Platelet Activation Is Required For Anti-gbm Antibody-inducementioning
confidence: 97%
See 1 more Smart Citation
“…Apyrase is an ectoenzyme that rapidly metabolizes ADP and adenosine triphosphate (ATP) released from activated platelets and endothelial cells, thereby minimizing ADP-dependent platelet activation and recruitment. 38 Apyrase treatment had no effect on platelet accumulation in anti-GBM antibody-treated mice ( Figure 9A). In contrast, apyrase treatment significantly decreased the number of adherent leukocytes in response to anti-GBM antibody ( Figure 9B).…”
Section: Platelet Activation Is Required For Anti-gbm Antibody-inducementioning
confidence: 97%
“…37 Other inhibitory molecules used were as follows: goat polyclonal antibody against mouse fibrinogen (Nordic Immunology, Tiburg, Netherlands; 4 mg/kg) 20 ; YN1/1.7.4, a rat monoclonal antibody against murine ICAM-1 (grown from hybridoma; 200 g/ mouse); RB6-8C5, a monoclonal antibody against Gr-1 (grown from hybridoma; 150 g/mouse); and apyrase, an enzyme that metabolizes adenosine diphosphate (ADP), thereby limiting platelet activation (Sigma-Aldrich, Castle Hill, NSW, Australia; 0.2 U/g). 38 For control experiments, isotype antibodies used included rat IgG 2a and IgG 2b (BD Biosciences, San Diego, CA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…With regard to mosquito sialomes, this type of enzyme was previously found solely in Culex quinquefasciatus, and the recombinant enzyme characterized . It is to be noted that transcripts coding for members of the 5′-nucleotidase family, associated with salivary apyrase in mosquitoes (Champagne et al 1995, Sun et al 2006, have not been identified in O. triseriatus, although it was abundantly expressed in Aedes aegypti and Aedes albopictus transcriptomes, and the nucleotidase activity previously reported for O. triseriatus salivary gland homogenates was similar to that of Ae. aegypti in amounts and kinetic characterisitics (pH and divalent cation dependence) (Reno and Novak 2005).…”
Section: Proteins Belonging To Ubiquitous Protein Familiesmentioning
confidence: 82%
“…Uno de los parámetros experimentales que afecta el inmunoensayo es la temperatura de incubación de Ag-Ac. Diversas temperatura de incubación han sido reportadas en la literatura, variando de 25 a 37 o C (Sun et al 2006;Santandreu et al,1997). Como es bien sabido, la temperatura óptima de la inmunoreacción es 37 o C. Las proteínas exhiben una mejor actividad para el rango de temperatura entre 20 a 25 o C. A temperaturas superiores puede ocurrir un decaimiento de su actividad y especificidad.…”
Section: Optimización De Las Condiciones Del Análisisunclassified